Recurrent c.G1636A (p.G546S) mutation of COL2A1 in a Chinese family with skeletal dysplasia and different metaphyseal changes: a case report - Jing Chen; Xiaomin Ma; Yulin Zhou; Guimei Li; Qiwei Guo (BMC, 2017)
Abstract Background Mutations in the COL2A1 gene cause type II collagenopathies characterized by skeletal dysplasia with a wide spectrum of phenotypic severity. Most COL2A1 mutations located in the triple-helical region, and the glycine to bulky amino acid substitutions (e.g., glycine to serine) in the Gly-X-Y repeat were identified frequently. However, the same COL2A1 mutations are associated with different phenotypes and the genotype-phenotype relationship is still poorly understood. Therefore, the studies of more patients about the recurrent mutations in COL2A1 will be needed for further research to provide more comprehensive clinical and genetic data. In this paper, we report a rare recurrent c.G1636A (p.G546S) mutation in COL2A1 associated with different metaphyseal changes in a Chinese family. Case presentation The proband (III-3) was the second child of the family with skeletal dysplasia. She was 2 years and 3 months old with disproportional short stature, short neck, pectus carinatum, genu varum, bilateral pes planus, and obvious waddling gait. Notably, she displayed severe metaphyseal lesions, especially typical "dappling" and "corner fracture" appearance, whereas no particular metaphyseal involvement was detected in the proband's mother (II-3) and elder sister (III-2) in the family. We identified a heterozygous mutation (c.1636G > A) in COL2A1 in the three patients, causing the substitution of glycine to serine in codon 546. Although the same mutation has been reported in two previous studies, the phenotypes of the previous patients were different from those of our patients, and the characteristic "dappling" and "corner fracture" metaphyseal abnormalities were not reported previously. Conclusions In this study, we identified a c.G1636A (p.G546S) mutation in the COL2A1 associated with different metaphyseal changes, which was never reported in the literature. Our findings revealed a different causative amino acid substitution (glycine to serine) associated with the "dappling" and "corner fracture" metaphyseal abnormalities, and may provide a useful reference for evaluating the phenotypic spectrum and variability of type II collagenopathies.